Intervensi Latihan Pernapasan dan Fisioterapi Dada Terstruktur bagi Lansia: Strategi Meningkatkan Fungsi Kardiorespirasi melalui Program Pengabdian Masyarakat - Angria Pradita; Nike Sefrida Agus Widyaningsih; Dimas Kurniawan; Mardan Sangkaka; Tiara Putri Kusuma W; Muhammad Ulil A; Angelina Stephanie; Amelia Putik M (Jurnal Pengabdian Pemersatu Bangsa, 2025)
The decline in cardiorespiratory function is a common part of the physiological aging process in the elderly, often leading to reduced activity capacity and decreased quality of life. Cardiopulmonary physiotherapy, particularly through structured breathing exercises, has been proven to improve lung capacity, oxygenation, and physical function in older populations. This study aimed to evaluate the effectiveness of structured respiratory physiotherapy interventions—diaphragmatic breathing, pursed-lip breathing, and thoracic expansion—in improving cardiorespiratory function among elderly individuals with respiratory disorders in Gondowangi and Sidorahayu Villages, Wagir Subdistrict. Methods: The community service project was conducted over the course of July 2025, involving three elderly participants diagnosed with COPD, asthma, and pneumonia. Interventions were delivered during four home visits through a guided home program. Evaluations included vital signs, auscultation, spirometry, and pulse oximetry at each stage of the intervention. Results: The results demonstrated significant improvements in clinical parameters, including increased oxygen saturation (SpO₂) from an average of 90% to 96–98%, reduced respiratory rate, improved expiratory volume on spirometry, and a decrease in abnormal breath sounds (wheezing and crackles). The most notable improvements were observed in the COPD patient, followed by those with pneumonia and asthma. Conclusion: Structured breathing exercises are effective in enhancing cardiorespiratory function in elderly patients with respiratory conditions. These interventions are simple, feasible for independent practice, and hold strong potential for sustainable implementation within community settings with the support of local health workers and cadres